2018
DOI: 10.1038/s41467-018-07470-w
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-vasculature development via endothelial-to-mesenchymal transition after radiotherapy controls CD44v6+ cancer cell and macrophage polarization

Abstract: It remains controversial whether targeting tumour vasculature can improve radiotherapeutic efficacy. We report that radiation-induced endothelial-to-mesenchymal transition (EndMT) leads to tumour vasculature with abnormal SMA+NG2+ pericyte recruitment during tumour regrowth after radiotherapy. Trp53 (but not Tgfbr2) deletion in endothelial cells (ECs) inhibited radiation-induced EndMT, reducing tumour regrowth and metastases with a high CD44v6+ cancer-stem-cell (CSC) content after radiotherapy. Osteopontin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 59 publications
3
91
0
Order By: Relevance
“…42 and 43 ). In tumors, EndoMT has been found to be a source of cancer-associated fibroblasts ( 44 ) and was recently shown to promote lung fibrosis and tumorigenesis ( 45 ), as well as protumorigenic macro phage polarization ( 46 ).…”
Section: Endothelial-to-mesenchymal Transition (Endomt)mentioning
confidence: 99%
“…42 and 43 ). In tumors, EndoMT has been found to be a source of cancer-associated fibroblasts ( 44 ) and was recently shown to promote lung fibrosis and tumorigenesis ( 45 ), as well as protumorigenic macro phage polarization ( 46 ).…”
Section: Endothelial-to-mesenchymal Transition (Endomt)mentioning
confidence: 99%
“…EndMT is also related to radiation therapy. Choi et al (2018) showed that radiation could induce EndMT, which triggered tumor-associated macrophage (TAM) polarization toward an M2 phenotype and resulted in radiation resistance. Additionally, CAFs can support immune evasion and act as an immunosuppressive agent in cancer immunotherapy, by inducing the secretion of multiple chemokines and cytokines, such as TGF-β and IL-6/8/13, and thereby inhibit the antitumor immune response.…”
Section: Endmt In Cancermentioning
confidence: 99%
“…Tight junctions consist primarily of intrinsic transmembrane proteins, scaffold proteins, and regulatory molecules between cells [10]. Studies have shown that tight junctions between vascular endothelial cells play a critical role in the BBB [11]. Thus, most studies on the effects of radiation on blood vessels have focused on endothelial cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput technology enables comprehensive monitoring of biological systems and provides an entry point to clarify molecular mechanisms that are involved in cell responses to environment changes. Therefore, we investigated the effect of a dose of X-rays (20 Gy) on transcripts in rat BMECs [11,12] to provide a theoretical basis for understanding the molecular mechanisms underpinning radiotherapy-induced brain edema. The results of the present study may also offer potential targets for future drug development.…”
Section: Introductionmentioning
confidence: 99%